THE INFLUENCE OF CHILD-FRIENDLY SCHOOL POLICIES AND THE ROLE OF SCHOOL COMMITTEES ON THE FORMATION OF POSITIVE STUDENT CULTURE AT GAYAM ELEMENTARY SCHOOL AND RANGGEH ELEMENTARY SCHOOL, GONDANGWETAN DISTRICT - Sofeyah; Ahmad Thohirin; M. Furqon Wahyudi (Yayasan Amanah Nur Aman, 2026)
This study explores real challenges at the elementary school level, such as declining teaching motivation, static instructional methods, and barriers to adopting information technology. Furthermore, conventional academic supervision procedures are often deemed ineffective due to minimal follow-up to facilitate independent teacher professional development. The primary objective of this study is to explore the implementation phase of coaching techniques in supervision activities, map obstacles in the field, and measure their impact on teacher effectiveness at SDN Ranggeh and SDN Gayam in Pasuruan Regency. This investigation employed a qualitative methodology with a multi-site study design. Primary data were collected through in-depth interviews with principals, supervisors, and teaching staff. Secondary data were obtained through direct observation and review of documents related to supervision planning and results. The data analysis process was systematically managed, encompassing reduction, presentation, and drawing conclusions to ensure the validity of the research results. The research findings demonstrate the successful integration of a coaching-based collaborative supervision model using the TIRTA (Goal, Identification, Action Plan, Responsibility) and GROW (Goal, Reality, Options, Will) frameworks. The application of this approach has been proven to optimize the pedagogical and professional competencies of educators, foster internal motivation, and stimulate learning innovations that contribute to improving the quality of education and developing student character.